2020
DOI: 10.1080/1081602x.2020.1719859
|View full text |Cite
|
Sign up to set email alerts
|

Marriages among people with disabilities in 19th-century Sweden: marital age and spouse’s characteristics

Abstract: While marrying was an expected event in 19th-century Western society and has been subject to much historical research, there are few studies on how disabilities influenced people's marriage patterns and spouse selection. The aim of this analysis is to contribute clarification on this issue by examining with whom disabled men and women married and the marital age and socio-demographic characteristics of them and their spouses. In total, 188 disabled individuals born in the first half of the 19th century and who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…On the other hand, Vikström, Haage, and Lundevaller (2020) study revealed that men and women with disabilities are reluctant to marry each other. They also mentioned that disability significantly impeded people's marriage prospects as a possible consequence of social marginalization in society.…”
Section: Sense Of Belongingmentioning
confidence: 99%
“…On the other hand, Vikström, Haage, and Lundevaller (2020) study revealed that men and women with disabilities are reluctant to marry each other. They also mentioned that disability significantly impeded people's marriage prospects as a possible consequence of social marginalization in society.…”
Section: Sense Of Belongingmentioning
confidence: 99%
“…In recent years, Lotta Vikström has continued to investigate the lives of people with disabilities. This is done in an interdisciplinary research group, funded by the ERC (Junkka, Sandström, & Vikström, 2020;Vikström, Haage, & Häggström Lundevaller, 2020;. In this project, disability is studied from many different aspects, in both historical time and contemporary society, and with both quantitative and qualitative sources.…”
Section: Social History and The Study Of Marginalised Groups In Societymentioning
confidence: 99%
“…This study provides statistical evidence that individuals born in Sweden during the 1970s who received disability pensions during young adulthood experienced significantly lower odds to marry or cohabit. In another contribution (Vikström et al, 2020, this issue), the authors discuss some previous life course results using Cox regression models on digitised parish registers in which ministers reported impairments (Haage et al, 2017). The disability outcome is shown in Figure 1 in terms of hazard ratios (the first pair of bars).…”
Section: Long-term Trends In Disability and Partnershipmentioning
confidence: 99%